Evidence of Climate Change Impact on Quantity of Rice-Planted Areas in Panama - SUAREZ, Ronny (Journal of Environmental Management and Tourism; Vol 15 No 4 (2024): JEMT, Volume XV, Issue 4(76), Winter 2024DO - 10.14505/jemt.v15.4(76).04, 2024)
This paper provides statistical evidence of a positive correlation between anomaly precipitation and the variation of planted hectares of rice. Panamanian farmers reduce planted areas of rice when they experience lower levels of rain.